Clinical Implications of the Coexistence of Anemia and Diabetes Mellitus in the Elderly Population. (18th October 2021) - Michalak, S. S.; Wolny-Rokicka, E.; Nowakowska, E.; Michalak, M.; Gil, L.
Abstract : Diabetes mellitus (DM) and also anemia are common in the elderly and have a negative impact on the clinical outcomes of patients. The coexistence of anemia and DM seems to be insufficiently recognized; therefore, the aim of our study is to analyze the incidence and clinical consequences of this coexistence, including mortality, in the population of people aged ≥60. A retrospective study was conducted on 981 primary care clinic patients aged ≥60 during 2013-2014. The prevalence of coexistence of DM and anemia (defined in accordance with WHO) and data on the incidence of comorbidities, hospitalization, medical procedures, and all-cause mortality were analyzed. In the study population, 25% had DM, while 5.4% had both DM and anemia. Peripheral artery disease (PAD) was found in 48 patients (4.89%) of the entire study population, more often in men (p < 0.001 ). Diabetic patients with anemia compared to nonanemic diabetics had more comorbidities (median 4 (4, 5) vs. 3 (2–4); p < 0.001 )—PAD more often (p = 0.004 ), more hospitalization (median 2 (0–11) vs. 0 (0–11); p < 0.001 ), and more frequent medical procedures (e.g., percutaneous coronary intervention (p < 0.001 ), coronary artery bypass surgery (p = 0.027 ), arteriography (p < 0.001 ), and bypass surgery or endovascular treatments of lower limb ischemia (p < 0.001 )). The cumulative survival of patients with both DM and anemia vs. nonanemic diabetics at 36 months was 86.4% vs. 99.3% (p < 0.001 ). A multivariate logistic regression model showed anemia to be a significant risk factor for death in diabetic patients (p = 0.013 ). Patients with both DM and anemia have more comorbidities than nonanemic diabetic patients; they are more often hospitalized, require medical procedures more frequently, and are at a higher risk of death. Effective treatment of anemia in patients with DM is advisable and may well improve the prognosis of patients.